Morphological and Molecular Evidence for a New Species of Dianthus (Caryophyllaceae) from Turkey - Koç, Murat (Phytotaxa, 2020)
The Flora of Turkey includes 88 Dianthus taxa. Some interesting populations belonging were observed in the Sivas province (C-Turkey). On the basis of both morphological and molecural investigations the Sivas population was here described as a new species for the science, named Dianthus hamzaoglui. A diagnosis, detailed description, distribution area, habitat, and IUCN assessment, as well as original photos were provided, as well as a comparison with the related D. burdurensis.